STUDENTS’ SPEAKING SKILL INMEDICAL ENGLISH SUBJECT AT MIDWIFERY STUDENTS - Pipit Rahayu; Rosi Lestari (JEE (Journal of English Education), 2019)
This purpose of the research was to find out students’ speaking skill in midwifery students at third semester students of midwifery program in university of Pasir Pengraian. The kind of this research was descriptive qualitative only focus describing the data. The data got from documentation speaking practice of medical English. The researcher took the data fromdocumentation video. In collecting the data the researcher useddocumentation and speaking test to got the data. In analyzing the data the researcher used the components of speaking such as : pronunciation, grammar, vocabulary, fluency and comprehension. The population of the research was third semester students academic 2018/2019 Midwifery StudyProgram, the sample of this research were 14 students. Based on the result of analysis, the researcher found 1 student (7%) had good score, 5 students (36%) had average score and 8 students (57%) had fair score.